(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article main directions of constitutional reform open up in Republic of Kazakhstan. In opinion of author new constitutional reform will touch the wide circle of questions. It will entail considerable reform of all constitutional legislation. Key words: Constitution, рефрмa, appeal, President, Parliament, human rights.